Climate Change Education in the Context of Education for Sustainable Development: Rationale and Principles. (March 2015) - Mochizuki, Yoko; Bryan, Audrey
Although the role of education in addressing the challenges of climate change is increasingly recognized, the education sector remains underutilized as a strategic resource to mitigate and adapt to climate change. Education stakeholders in many countries have yet to develop a coherent framework for climate change education (CCE). This article underscores the critical role that education can and should play in addressing and responding to climate change in all of its complexity. It provides rationales as to why CCE should be addressed in the context of Education for Sustainable Development (ESD). Advancing CCE in the context of ESD, or Climate Change Education for Sustainable Development (CCESD), requires enhancement of learners' understanding of the causes and consequences of climate change and their readiness to take actions to address it. The article presents key organizing principles of CCESD and outlines key knowledge, skills, attitudes, dispositions and competences to be fostered through it.